AB0108 Decreased expression of PTPN22 gene in patients with rheumatoid arthritis carrying the risk allele of PTPN22 RS2488457 polymorphism. (15th June 2017) - Remuzgo-Martínez, S; Castañeda, S; Corrales, A; Genre, F; Lόpez-Mejías, R; Moreno-Fresneda, P; Ubilla, B; Mijares, V; Portilla, V; González-Vela, J; Pina, T; Ocejo-Vinyals, G; et al.
Abstract : Background: Mutations in the protein tyrosine phosphatase non-receptor 22 ( PTPN22 ) gene are associated with numerous connective tissue and autoimmune diseases [1]. In particular, PTPN22 has been recognized as the main non-HLA genetic risk factor involved in rheumatoid arthritis (RA) susceptibility [2]. Moreover, it has been suggested that PTPN22 modulation may influence on inflammatory processes associated with RA [3, 4]. Objectives: To determine if PTPN22 (rs2476601, rs33996649 and rs2488457) polymorphisms, associated with RA, may influence on PTPN22 expression in RA patients compared to healthy controls. Moreover, the association between PTPN22 expression in patients with RA and their clinical characteristics was studied. Methods: PTPN22 messenger RNA (mRNA) expression was quantified by quantitative real-time PCR in peripheral blood samples from 42 RA patients and 24 healthy controls. PTPN22 rs2476601 (G>A), PTPN22 rs3399649 (C>T), and PTPN22 rs2488457 (C>G) single-nucleotide polymorphisms (SNP) were genotyped by TaqMan SNP genotyping assays. Differences in PTPN22 expression between patients and controls were analyzed by Student's t test, according to their genotype. Correlation coefficients were also assessed between PTPN22 expression in RA patients and their clinical characteristics. Results: A significant down-regulation of PTPN22 expression in patients with RA carrying PTPN22 rs2488457 risk allele (G) compared to controls was observed (relative mean values of PTPN22 mRNA levels ± standard deviation: 2.93±0.76 vs 4.33±0.63, p=0.0004). Furthermore, an inverse relationship between PTPN22 expression and disease duration (r=-0.38, p=0.03) was found. These results were adjusted by sex, age at time of study and cardiovascular risk factors. Conclusions: Our study shows for the first time that the risk allele of PTPN22 rs2488457 polymorphism influences on the down-regulation of PTPN22 in patients with RA. This result suggests a transcriptional suppression of PTPN22 gene in RA, which in turn may play an important role in disease diagnosis and progression. References: Stanford and Bottini. Nat Rev Rheumatol 2014, 10(10):602–11. Messemaker et al. J Autoimmun 2015, 64:74–81. Ronninger et al. Genome Med 2012;4(1):2. Díaz-Gallo and Martín. Genome Med 2012;4(2):13. Acknowledgements: This study was supported by European Union FEDER funds and "Fondo de Investigaciόn Sanitaria" (PI12/00060 and PI15/00525) from "Instituto de Salud Carlos III" (ISCIII, Health Ministry, Spain). It was also partially supported by RETICS Programs RD12/0009 and RD16/0012 (RIER) from ISCIII. SR-M is supported by fund from the RETICS Program (RIER) (RD16/0012/0009). FG is a recipient of a Sara Borrell postdoctoral fellowship from ISCII (CD15/00095). RL-M is supported by a "Miguel Servet tipo-I" contract from ISCIII (CP16/00033). BU is supported by funds from the RETICS Program (RIER) (RD12/0009/0013) from ISCIII (Health Ministry, Spain). Disclosure of Interest: None declared